SHARIA BANKING REGULATIONS CONCERNING MURABAHAH FINANCING IN INDONESIA - Heru Kuswandito; Barkah Islamiati; Kartika Sharaswati (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2021)
Islamic banks as intermediaries for financial transactions, and provide a product in the form of financing and services for customers without usury which is different from conventional banks using interest or usury. In each of its products, the bank has legal regulations that exist in Indonesia, and in carrying out it must have a sharia supervisory board sent by the DSN-MUI, so that the product does not conflict with the Qur'an and Hadith, because Islamic banks must comply with provisions of the Qur'an and hadith that prohibit usury. The product that is most in demand is the sale and purchase contract, namely Murabaha. Murabahah is a sale and purchase contract in which the bank provides financing in the form of goods to the customer along with an initial agreement. The bank buys directly from the direct supplier and will give it directly, but the bank will give the price according to the initial agreement. The murabahah product itself is also believed to provide benefits to both the Islamic bank itself and the customer, to this customer it can also provide a small risk.